DETERMINAN KINERJA PERAWAT DALAM PENERAPAN PATIENT SAFETY DI RS IMELDA PEKERJA INDONESIA TAHUN 2020 - Puput Melati Hutauruk; Rahmawani Fauza (Jurnal Ilmiah Keperawatan IMELDA, 2021)
The performance of nurses in providing nursing services is an integral part of health care. The factors that affect the performance of nurses also play a role in the effectiveness of the application of patient safety in nursing care, including the motivation factors of nurses and the workload of nurses. Nurses work motivation will be able to influence the implementation of patient safety. The workload of nurses can also have an impact on the optimization of the provision of service care. The general objective in this study was to determine the determinants of nurse performance in the application of patient safety at the Imelda Worker Hospital of Indonesia. The research method used was a quantitative study with a cross sectional study approach. The population in this study were all inpatient nurses at Imelda Hospital Medan, totaling 217 people, with a total sample of 140 people according to the specified incusion criteria. Data analysis using frequency distribution and chi square test. Based on the results of the study, it was found that there was an influence on the work motivation of nurses in the application of patient safety at Imelda Hospital, Indonesian Workers with p-value = 0.000 <0.05 and there was also an influence on the workload of nurses in the application of patient safety at Imelda Hospital, Indonesian Workers with p-value = 0.000. <0.05. In connection with efforts to improve the performance of nurses in the application of patient safety at the Indonesian Worker Imelda Hospital, it is necessary for the head of care to pay more attention to matters relating to providing motivation and rules regarding the workload of nurses so that nurses can maximize their performance.